PENGARUH CURRENT RATIO (CR), TOTAL ASSET TURNOVER (TATO) DAN DEBT TO ASSET RATIO (DAR) TERHADAP NET PROFIT MARGIN (NPM): (Studi Pada PT Japfa Comfeed Indonesia Tbk Periode 2015-2024) - Alfinah Damayanti; Achmad Ludvy (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the influence of Current Ratio (CR), Total Asset Turnover (TATO), and Debt to Asset Ratio (DAR) on Net Profit Margin (NPM). The research method used is a quantitative approach with multiple linear regression analysis. The research data was analyzed using STATA. The results of the partial test (t-test) showed that Current Ratio (CR) and Total Asset Turnover (TATO) had no significant effect on Net Profit Margin (NPM), while Debt to Asset Ratio (DAR) had a negative and significant effect on Net Profit Margin (NPM). The results of the simultaneous test (F test) show that the Current Ratio (CR), Total Asset Turnover (TATO), and Debt to Asset Ratio (DAR) still cannot have a significant impact on the Net Profit Margin (NPM) at the level of 5%. With an R-squared value of 68.13%, the variation in Net Profit Margin (NPM) can be explained by the variables Current Ratio (CR), Total Asset Turnover (TATO), and Debt to Asset Ratio (DAR). Meanwhile, the remaining 31.87% were influenced by other variables outside the research model.